Laser-Induced Breakdown Spectroscopy for Determination of Toxic Metals in Fertilizers: emphasis on Lead - Salloom, Hussein T.; Hamad, Tagreed K.; Rajab, Fatema H. (Iraqi Journal of Science, 2022)
The present work aims to evaluate the content of some toxic metals in chemical and organic fertilizers purchased from local markets in Baghdad, Iraq. The analysis was performed by laser-induced breakdown spectroscopy (LIBS) system. The emission spectral lines of lead (Pb), chromium (Cr), cadmium (Cd) and cobalt (Co) have been recorded to determine the best peak representing each element according to the NIST database. The validity of the LIBS procedure was checked by cross-validating the obtained results using atomic absorption spectroscopy (AAS) with a maximum relative error of 5.3%. Moreover, for qualitative analysis, Pb I 296.64 nm emission line was determined to be superior for the evaluation of lead content in terms of three calibration methods: the external standard (ES), the internal standard (IS), and the multiple linear regression (MLR). The linear correlation coefficient values were : 0.94, 0.97 and 0.992, respectively. LIBS results based on the multiple linear regression (MLR) model have demonstrated better performance and were adopted in the assessment of the Pb content in solid fertilizer samples.